Forensic veterinary examination and assessment of reproductive damage and pregnancy termination in animals caused by sharp and blunt objects - Yatsenko, I.; Kozachok, V. (Scientific Progress & Innovations, 2025)
The article analyzes the issue of forensic veterinary examination and assessment of reproductive damage and pregnancy termination in animals caused by sharp and blunt objects. The issues of traumatic loss of reproductive capacity in animals, their traumatic abortion, traumatic amputation of genitals are discussed, as well as the determination of the severity of damage inflicted on the animal health and mutilation. Additionally, the algorithm for conducting forensic veterinary examinations in cases of genital injuries is outlined. It is argued that the objects of forensic veterinary examination and assessment of reproductive damage and pregnancy termination due to damage are vertebrate animals. The subjects of such research are forensic veterinary experts. The subject of forensic veterinary examination is a set of factual data and circumstances of criminal proceedings (cases) related to the determination by a forensic veterinary expert of the damage inflicted on the health and life of an animal in connection with reproductive damage and pregnancy termination due to injury, by means of a multidisciplinary study of objects as information carriers, using appropriate means (methods) for the resolution of diagnostic and situational tasks. It is proposed that in order to determine reproductive damage in an animal, it is necessary to establish a causal relationship between the injuries inflicted on the animal, determined by physical methods of forensic veterinary examination, and the fact of reproductive damage or pregnancy termination. It has been proven that pregnancy termination in a female can be the result of direct damage to the uterus with fetuses, other genital organs, as well as a consequence of the female’s death due to fatal injury, not directly related to the injury of the genital organs. In the context of forensic veterinary examination, pregnancy termination in animals due to damage of any etiology, regardless of gestational age, is assessed based on the damage to the uterus (where the fetuses developed) or other genital organs. It is substantiated that the loss of reproductive organs as a result of damage is a mutilation of an animal if, when interacting with the external environment, it will subsequently cause a restriction of manifestations of vital activity on a par with other animals of the same species. However, it has been shown that the loss of an organ, if it is removed by surgical intervention for economic or aesthetic purposes, for example, castration of an animal, ovariectomy, hysterectomy, tail amputation, decortication, ear resection, etc., is not a subject of forensic veterinary examination.